Moderation and Agricultural Education for Cultural Communities in the Era of Technology 5.0 - Agus Darwanto; Elyne Kusuma Mahardika; Rully Charitas Indra Prahmana; Ani Susanti (Journal of Pedagogy and Education Science, 2026)
The rapid evolution of Technology 5.0 has revolutionized agriculture through microcontroller-based sensor systems that provide real-time climate monitoring. However, a persistent gap exists between these technological advancements and the traditional farming practices of culturally rooted communities, such as those in Cilacap Regency, Indonesia, who continue to rely on indigenous knowledge and customary leaders for agricultural decision-making. To address this disconnect, this study introduces the novel Agroclimatic Caping device, designed to harmonize modern agroclimatology technology with local wisdom. The research aims to develop and implement an IoT-based agroclimatic monitoring system using the Research and Development (R&D) method, integrating ESP8266, BME680 sensors, Blynk application, and AI-powered processing. The system delivers real-time data—including humidity, temperature, air pressure, dew point, and gas concentration—directly to farmers’ smartphones and supports decision-making through AI chatbots. This innovation promotes sustainable agricultural productivity while preserving cultural traditions, offering a replicable model for technology adoption in rural communities.